Sleep, recovery, and athletic performance: A brief review and recommendations - Bird, S. P. (Strength and Conditioning Journal, 2013)
Sleep has been identified as an important factor contributing to optimal athletic performance. However, the psychosociophysiological stresses placed on elite athletes may result in an inability to gain appropriate sleep. Improving an athlete's sleep hygiene is seen as a key strategy that could have powerful implications for athletic performance. Therefore, the purpose of this article is to (a) overview the impact of sleep on recovery and athletic performance; (b) outline sleep hygiene strategies; and (c) provide sleep recommendations for athletes and coaches. The sleep hygiene strategies presented in this article represent a practical approach to improve sleep in elite athletes.